The Boardroom Effect: Understanding Director Remuneration Disclosure in Malaysia - Esa, Elinda; Zahari, Abdul Rahman (Journal of Technology Management and Business, 2025)
Stakeholders’ concern over director remuneration disclosure has remained prominent following high-profile corporate scandals and financial crises, such as the Enron collapse and the 2009 global financial crisis. Despite the structural and financial challenges faced by firms, many directors continue to receive substantial pay packages, prompting scrutiny from regulators, investors, and the public. This study aims to examine the level of transparency in director remuneration disclosures among Malaysian public-listed companies (PLCs) and to explore the influence of corporate governance attributes particularly board characteristics on disclosure practices. A content analysis approach was employed, utilizing a director remuneration transparency scoreboard to assess the annual reports of 100 Malaysian PLCs. Data was collected from publicly available corporate reports, and board characteristics such as size, independence, and ethnicity were examined using secondary data. The findings reveal that board ethnicity and company size significantly influence the extent of directors’ remuneration disclosure. These insights contribute to the ongoing discourse on corporate transparency and suggest that future studies consider ethical dimensions as potential determinants of disclosure practices.